Magnetocaloric materials for energy efficient cooling. (5th January 2017) - Lyubina, Julia
Abstract: Solid-state magnetic cooling near room temperature has recently gained a prominent position among alternative cooling technologies that are deemed to have higher energy efficiency compared to vapour compression. This prospect has surged a rapid growth of the area of magnetocaloric materials. Although several breakthroughs were achieved, the extensive study revealed a number of challenges in the effective deployment of the magnetic refrigerants. This review focuses on fundamentally and technologically relevant aspects of the cooling with magnetocaloric materials. A critical evaluation of magnetic refrigerants and progress made in improvement of their performance is provided. Future development trends in the field of materials for the solid state cooling are highlighted.